Multi-Scale Numerical Analysis of the Effect of Microstructural Features on the Mechanical Behavior of Polycrystalline Ti-6Al-4V Alloy - BENMESSAOUD, Fatna; VELAY, Vincent; CHEIKH, Mohammed; VIDAL, Vanessa; BOHER, Christine; RÉZAÏ-ARIA Farhad (Engineering Transactions, 2019)
The present work aims to model the influence of microstructural features of Ti-6Al-4V titanium alloy on its mechanical behavior. A multi-scale approach based on crystal plasticity is considered. The elasto-viscoplastic constitutive equations of Meric-Cailletaud are modified to take into consideration the effect of the grain size by introducing the Hall-Petch relationship at the local scale. This modified model is coupled with finite element calculations under small strain assumption to simulate the monotonic mechanical behavior of Ti-6A-4V at local and global scales. It is shown that the mechanical behavior of Ti-6Al-4V is drastically dependent upon the material features. Strong crystallographic texture can result in the formation of hardened and less hardened areas. Moreover, by increasing the grain size scattering, the heterogeneously deformed areas are multiplied. By decreasing the average grain size, the yield strength increases. It is observed that the effects of grain size, grain size scattering and crystallographic texture are coupled.